2010
DOI: 10.1590/s1676-06032010000400032
|View full text |Cite
|
Sign up to set email alerts
|

Flora arbustiva-arbórea de três áreas ribeirinhas no semiárido paraibano, Brasil

Abstract: . O levantamento das três áreas registrou um total de 91 espécies, das quais 68 ocorreram na área do riacho do Cazuzinha, 62 no riacho dos Mares e 56 no riacho do Farias. As famílias com maior número de espécies e de gêneros foram Fabaceae, Euphorbiaceae e Rubiaceae. Do total de espécies registrado para as três áreas, 15 estão presentes nas listas relacionadas para matas ciliares de outros estados do Brasil, 26 são endêmicas da Caatinga e 10 foram exclusivas. Analisando a similaridade florística entre as áreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
1
5
0
14
Order By: Relevance
“…These studies showed, however, a greater emphasis on diseases related to the respiratory and digestive systems and encountered anything from 36 to 140 species, mostly indicating greater diversity in the families Fabaceae and Euphorbiaceae. This lies in agreement with a higher register of these families in floristic and phytosociological surveys carried out in the region [ 22 24 ]. These studies are spread over different types of traditional communities in Brazil, e.g., farmer communities [ 25 – 27 ], indigenous populations [ 28 , 29 ], quilombolas [ 30 , 31 ], riparian populations [ 32 ], and caiçaras [ 33 ].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…These studies showed, however, a greater emphasis on diseases related to the respiratory and digestive systems and encountered anything from 36 to 140 species, mostly indicating greater diversity in the families Fabaceae and Euphorbiaceae. This lies in agreement with a higher register of these families in floristic and phytosociological surveys carried out in the region [ 22 24 ]. These studies are spread over different types of traditional communities in Brazil, e.g., farmer communities [ 25 – 27 ], indigenous populations [ 28 , 29 ], quilombolas [ 30 , 31 ], riparian populations [ 32 ], and caiçaras [ 33 ].…”
Section: Introductionsupporting
confidence: 88%
“…The use of 36 trees, 19 shrubs, and 11 lianas species can also be considered representative when compared to data obtained from floristic and phytosociological studies in areas of Caatinga which mention 17 to 91 shrub-tree species or woody species [ 23 , 24 , 69 71 ]. Various studies on medicinal plants of the Caatinga have been published, and when only the woody species (shrubs and trees) and native species of this biome are observed, we found a similar number of species, with small variations.…”
Section: Resultsmentioning
confidence: 99%
“…Combretaceae family, which accounted for 25.4% of the individuals, was represented by two species: Combretum leprosum Mart. and Combretum monetaria Mart.. Fabaceae species have been found in riparian forest areas in the caatinga (Farias et al, 2017;Ferraz et al, 2006;Holanda et al, 2005;Lacerda et al, 2007Lacerda et al, , 2010Santos & Vieira, 2006;Silva FG et al, 2015;Souza & Rodal, 2010;Trovão et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…No Semiárido, as matas ciliares da região foram os primeiros locais a sofrer alteração na vegetação por serem áreas preferenciais para o cultivo agrícola no período colonial, de forma que, até hoje esse recurso natural é explorado inadequadamente (Souza e Rodal, 2010), embora sejam áreas de preservação permanente (APPs) protegida pela Lei nº 12.651/2012, o código Florestal Brasileiro (Brasil, 2012). Estes ambientes são extremamente importantes no que tange aos seus aspectos funcionais, ao passo que, são responsáveis pelo equilibro ecológico dos ecossistemas, assumindo uma função protetora estabelecendo interações que se estendem, a partir das margens, por vários metros a depender das características estruturais destes ecossistemas (Lacerda e Barbosa, 2018;Lacerda et al, 2010).…”
Section: Introductionunclassified